Principiul remunerării egale pentru o muncă de valoare egală [Articol] - Macovei, Tatiana („Garamont-Studio” SRL, 2012)
International standards of labor and gender equality in the payroll employees by the principle „equal pay for equal work or work of equal value”, means that work must be assessed according to objective criteria, regardless of who performs it - a man or a woman. Equal pay is not exclusively wages. The pay includes the basic salary and different supplements, such as premiums, overtime work, payment for sick leave, etc.
THE PRINCIPLE OF EQUAL PAY FOR WORK OF EQUAL VALUE
ПРИНЦИП РАВНОЙ ОПЛАТЫ ТРУДА ЗА ТРУД